Ice a memoir of gangster life and redemption ; from South Central to Hollywood - Ice T Rapmusiker 1958-; Century, Douglas 1964- (One World/Ballantine Books Trade Paperbacks, 2012)
The hip-hop artist and television star shares the story of his early life, marked by the deaths of his parents, his involvement in gangs, and the single-minded work ethic that enabled his rise to international fame
Keywords: Ice-T / (Musician); Rap musicians / United States / Biography; Rap musicians; United States / https://id.oclc.org/worldcat/entity/E39PBJtxgQXMWqmjMjjwXRHgrq; Rap musicians / Biography; Autobiographies; Biographies